Development of Micro Finance Institutions Model in the Rural Farmer Groups to Support Sustainable Agribusiness of Dairy Goats: A Pilot Study - Widiati, Rini (2014)
The purpose of this study was to develop a MFIs model to support sustainable agribusiness of dairy goats with a pilot study in Ngudi Makmur group in Sleman Regency of Yogyakarta. Method of RRA was used in thisresearchand continuedmentoringand coaching to the target groups. Thematerials of the research wasa capital to start MFIs activity of IDR. 15 million in the form revolving of funds as a loan. The interest of loan at 1.5%/month including for the cost of mentoring/coaching (0.3%) and to the capital increase of MFIs (1.2%). Descriptive analysis was used to determine there are the development of MFIs by measuring the increase of productive activity and revolving funds in the farmer group. The results of this research showed that most demand of fund (68.20%) in MFIs was used for productive activity so that there was the capital increase in the group. The building of the MFIs in the group can made a sustainable agribusiness of dairy goat. Behavior of farmers become more responsible towards the use of funds, measured from the smooth of loan repayment and installment.